Publisher Correction: Regional disparities in warm season rainfall changes over arid eastern–central Asia. Issue 1 (December 2018) - Dong, Wenhao; Lin, Yanluan; Wright, Jonathon; Xie, Yuanyu; Ming, Yi; Zhang, Han; Chen, Rensheng; Chen, Yaning; Xu, Fanghua; Lin, Namei; Yu, Chaoqing; Zhang, Bin; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.